2019
DOI: 10.2174/1874306401913010001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Latent Tuberculosis Infection among Healthcare Workers in a Low Incidence Country

Abstract: Background:Tuberculosis prevention is a major goal in the hospital setting. Because of the possible progression or reactivation of latent disease, the screening of healthcare workers is an important issue in the TB control program. The aim of the study was to assess the prevalence of LTBI (latent tuberculosis infection) and to evaluate the main risk factors related to this condition in a teaching hospital in Italy.Methods:We reviewed the data of a tuberculosis screening conducted on 3622 healthcare professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…In a recent meta-analysis, HCWs have been estimated to be both at high risk for active (A) and latent tuberculosis infection (LTBI) based on the results of epidemiological studies conducted in high and intermediate incidence countries [2]. A follow-up study carried out among a large number of North American hospital workers during the period 1995-2007 reported that TB incidence rates among HCWs were similar to those of the general population [6], foreign birth being the major risk factor of LTBI [7][8][9][10][11][12][13]. Moreover, a recent retrospective cohort study found an extremely low rate of Tuberculin Skin Test (TST) conversion among a large population of HCWs working in the low TB-incidence United States.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis, HCWs have been estimated to be both at high risk for active (A) and latent tuberculosis infection (LTBI) based on the results of epidemiological studies conducted in high and intermediate incidence countries [2]. A follow-up study carried out among a large number of North American hospital workers during the period 1995-2007 reported that TB incidence rates among HCWs were similar to those of the general population [6], foreign birth being the major risk factor of LTBI [7][8][9][10][11][12][13]. Moreover, a recent retrospective cohort study found an extremely low rate of Tuberculin Skin Test (TST) conversion among a large population of HCWs working in the low TB-incidence United States.…”
Section: Introductionmentioning
confidence: 99%
“…Table II shows fourteen studies with a total of 8,604 individuals from eight countries that were published between 2010 and 2020. Six from Italy (10,(19)(20)(21)(22)(23), two from India (24-25), and one, respectively, from Iran (26), Malaysia (27), South Korea (28), Uganda (29), Saudi Arabia (30) and South Africa (31). These studies were conducted from 2007 through 2019 and published from 2010 through 2020.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample size ranged from 79 to 2,466 subjects. Seven studies (19,20,22,(26)(27)(28)31) were conducted amongst the medical students (31.8%), three studies (23,24,30) amongst the nursing students (13.6%) and four studies (10,21, 24,28) reported on both the medical and nursing students (18.2%).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the symptoms of these diseases take time to manifest in the airways, which can prevent workers from realizing they have been exposed after symptoms begin [ 19 , 20 , 21 ]. For tuberculosis, which is caused by Mycobacterium tuberculosis (a Level 3 organism based on the biological risk it represents), public concern is based on the prevalence of the general population and healthcare workers that suffer from the disease [ 22 ]. In a report of WHO, it was estimated in 2015 that up to 2 billion people around the world suffer from a latent state of tuberculosis [ 23 ], which remains concerningly prevalent in low-risk countries, such as Italy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%